2018
DOI: 10.3892/etm.2018.6541
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of TRIM44 is an independent marker for predicting poor prognosis in epithelial ovarian cancer

Abstract: Tripartite motif-containing 44 (TRIM44) has been demonstrated to be important in tumor metastasis and progression. However, the expression pattern and prognostic value of the expression of TRIM44 in epithelial ovarian cancer (EOC) remain to be fully elucidated. In the present study, the aim was to investigate the expression and clinical role of TRIM44 in EOC. A total of 109 patients, who underwent primary surgery with the goal of maximal tumor resection followed by standard combination chemotherapy with carbop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 12 publications
2
22
0
Order By: Relevance
“…To elucidate the underlying mechanism of miR-192-5p involved in cell biological function in lung cancer, the TargetScan and miRNA databases were used to identify that miR-192-5p may combine with TRIM44. TRIM44 has been reported to be upregulated in many types of tumours, and TRIM44 is involved in tumour formation and progression 27,32,33 . Accumulating evidence has revealed that TRIM44 enhances the proliferation, migration, and invasion of lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…To elucidate the underlying mechanism of miR-192-5p involved in cell biological function in lung cancer, the TargetScan and miRNA databases were used to identify that miR-192-5p may combine with TRIM44. TRIM44 has been reported to be upregulated in many types of tumours, and TRIM44 is involved in tumour formation and progression 27,32,33 . Accumulating evidence has revealed that TRIM44 enhances the proliferation, migration, and invasion of lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past decades, efforts have been made to identify accurate biomarkers for gynecological cancer. For instance, upregulation of TRIM44 predicts poor prognosis in epithelial ovarian cancer (25), and LYL1 amplification predicts a shorter survival time of patients with UCEC (26). However, the prognosis of patients with gynecological cancer remains poor.…”
Section: Discussionmentioning
confidence: 99%
“…From a clinicopathological point of view, we previously showed that TRIM44 overexpression was associated with poor prognosis in testicular germ cell tumors . Other studies include an immunohistochemical (IHC) analysis that demonstrated that overexpression of TRIM44 was an independent predictor of poor prognosis in a series of 109 patients with epithelial ovarian cancer . Another IHC study revealed that TRIM44 overexpression was significantly associated with histological grade, depth of myometrial invasion and lymph node metastasis in endometrial carcinoma .…”
Section: Discussionmentioning
confidence: 99%
“…22 Other studies include an immunohistochemical (IHC) analysis that demonstrated that overexpression of TRIM44 was an independent predictor of poor prognosis in a series of 109 patients with epithelial ovarian cancer. 47 Another IHC study revealed that TRIM44 overexpression was significantly associated with histological grade, depth of myometrial invasion and lymph node metastasis in endometrial carcinoma. 48 In esophageal squamous cell carcinoma, overexpression of TRIM44 was associated with the status of lymph node metastasis and poor overall survival.…”
Section: Discussionmentioning
confidence: 99%